PENGEMBANGAN LKS BIOLOGI BERBASIS INQUIRY PADA MATERI SISTEM INDERA MANUSIA DI SMA - LAILATUS SADIYAH (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
One of learning tools or components which is developed to support improvement of student’s concept understanding in sensory system matter is worksheet. The aim of this 4D’s worksheet developmental study is to make a feasible, practice, efective worksheet and increase student’s learning mastery, implemented to 24 students using the one groups pretest-posttest design. The result of this study shows a good worksheet (3,2); Inquiry learning and activities observation (worksheet 01 and 02) is very good (3,7 and 3,53); student’s respon is very good (86,3); student’s learning mastery is mastered student. Conclussion of this experiment is a valid, practice, effective, and able to increase student’s learning mastery worksheet. Keywords: Developmental study, Inquiry Worksheet, sensory system, feasibility